LEADERSHIP IN HIGHER EDUCATION MANAGEMENT SYSTEM - Iqbal Faza Ahmad; Gusti Gede Diva Pari Sangga (Prodi Manajemen Pendidikan Islam FITK UIN Sunan Kalijaga Yogyakarta, 2022)
Failure to manage higher education will impact the loss of the higher education institution in producing quality human resources. This study explores leadership in the education management system at the Hindu Religion College (STAH) Dharma Sentana, Central Sulawesi. This research was conducted using a mixed-method with research subjects, all lecturers and employees who work at STAH Dharma Sentana Central Sulawesi, with as many as 41 respondents. Data were obtained through the distribution of questionnaires and interviews. The results of the partial analysis of research data indicate that two variables significantly affect the education management system: visionary and unifying. While the other three variables, namely empowering, controlling ratios and emotions, and integrity, in statistics do not significantly affect the education management system at STAH Dharma. Central Sulawesi Sentana. The results of the coefficient of determination of the value of R square indicate that the variation of the independent variables used in the model, namely visionary, unifying, empowering, controlling ratios and emotions, and integrity, contribute to or have an effect of 45.4% on the education management system variable. In this study, the role of the leader in improving the quality of the education management system that most dominantly influences is the unifying variable, where the leader can unify the diversity of employee characteristics. Leaders provide opportunities for employees to contribute to achieving organizational goals. This study provides a model of leadership in education management. This study provides a leadership model in education management in higher education to improve the quality of education.